Hiding in plain sight : youth mental illness [videorecording (DVD)] - Blistein, David; Coyote, Peter; Cieri, David (PBS, 2022)
A two-part, four-hour documentary that explores America's youth mental health crisis through the eyes of more than twenty young people, who speak about their lived experience with mental health challenges, from depression to addiction to suicide ideation.